Inflammation and cancer: friend or foe? - Turizo-Smith, Andrés David; Córdoba-Hernandez, Samantha; Mejía-Guarnizo, Lidy Vannessa; Monroy-Camacho, Paula Stefany; Rodríguez-García, Josefa Antonia (Frontiers in Pharmacology, 2024)
delves into the pivotal role of chronic inflammation in the onset and progression of various chronic pathologies, including cancer. We highlight the intricate connection between obesity, chronic inflammation, and cancer, emphasizing the urgency of seeking alternatives to modulate inflammation in the context of cancer. By elucidating specific etiological agents and mediators contributing to persistent inflammatory reactions in tumor development, we provide insights into viable therapeutic strategies for cancer treatment. Our review underscores the importance of further research for biomarkers in cancer diagnosis, prevention, and treatment. Additionally, we discuss the significance of population-based interventions, such as maintaining a healthy body weight and adopting an anti-inflammatory diet supplemented with nutraceuticals, in mitigating cancer risk. With a focus on innovative therapeutic approaches and the exploration of natural products and their derivatives as potential alternatives, our manuscript contributes to the advancement of knowledge in this critical area. We believe our work aligns seamlessly with the scope of the selected journal and specialty, offering valuable insights for its readership.